Peculiarities of Tour Guides’ Communication with Disabled People - Statkuvienė, Daiva (Information & Media, 2019)
Disabled people tend to go on tours more often. Neither guide training programs nor the guidebooks of arranging and doing tours include the peculiarity of working and communicating with disabled people. The features of how guides communicate with disabled people are researched in the paper. The peculiarities of doing a tour for physically, visually, auditorily, and mentally disabled people are found out. The sources of scientific literature and the standard of disabled people service are analyzed; conclusions are presented on how important it is for a guide to recognize clients’ disabilities, understand the culture of communicating with disabled people, and discover the most suitable methods of communication. The service of disabled tourists that satisfies their needs, ensures their dignity, integration, self-reliance, and equal rights should be the aim of any professional tour guide. This paper lays out some recommendations for the guide training program on including instructions for communicating with disabled clients.